Current Situation and Control Measures of Heavy Metal Pollution in Farmland Soil - Li, Wanying (Scientific Journal of Technology, 2025)
Heavy metal pollution of farmland soil can cause serious problems such as decreased farmland quality, reduced grain production, and farmland degradation, and pose a threat to human health through biological cycles. Soil pollution control has long been a hot topic of research for many scholars, and the study of soil heavy metal pollution remediation technology is a major part of soil remediation work. This article starts from the current situation of heavy metal pollution in soil in China, analyzes the main sources of heavy metal pollution in farmland soil, and proposes targeted measures for the remediation of soil heavy metal pollutants through physical, chemical, biological remediation, and joint remediation technologies, in order to provide reference and guidance for alleviating soil safety issues in farmland in China.